Procedimentos tradutórios e dimensões da figura feminina em Sonho de uma noite de verão, de William Shakespeare - Andrade, Mislainy Patricia de (2013)
This study is about translation procedures in A Midsummer Night´s Dream by William Shakespeare on its five translations published in Brazil by Carlos Alberto Nunes (1955), F. C. Medeiros Mendes and Oscar (1969); Beatriz Viégas-Faria (2001); Heliodora Barbara (2004) and Erick Ramalho (2006). Our intention here is also verifying in these translations, comparing to the source text, speeches that report the development of the women‟s profile in Shakespearean work in analysis. From the assumption that each translator has his own characteristics and style, we have checked in this study the translation strategies which had been chosen and used by each author in their translation process. We know that each translation was produced in different social and historical contexts, however, for a greater comprehension of its specificities, this study had as a theoretical basis, the methodological model of Lambert and van Gorp (1985), thereby, justifying with greater accuracy and efficiency the choices of each author‟s translation procedures. This analysis had been developed in three stages: (i) identifying fragments that address the woman‟s profile in Shakespeare work, (ii) checking fragments (in the target texts) of each possible statement or word, previously highlighted, about woman‟s profile, (iii) analyze the translation procedures observed before, and the general effects they may cause in different translations, in order to analyze how the translations may maintain, attenuate, intensify or omit, among other things, discursive aspects about the construction of the female profile once verified on the source text. Therefore, this study followed the scheme of strategies developed by MárciaParedesNunes (2007), it consists of translation strategies relevant for this research. Our theoretical referential is based on the Descriptive Translation Studies, about theories and approaches from authors such as Even-Zohar (1990), Toury (1980, 1995, 1998), Lefevere (1990) and Venuti (2002). We have noticed that all translators have tried to be as faithful as possible and keep in their translations the original proposal, always looking for equivalent terms between the source text and the target text, and worrying about the lexicon, the semantic and with the linguistic varieties present in the Shakespearean text, they also (re)create the play‟s scenic aspects. Whereas, the translation studies are still recent in Brazil, this research does not stop here. New studies will come contributing to the increase and diffusion of this new field of scientific and academic research.